2D bending (curvature) recognition based on a combination of a TFBG and an orthogonal TFBG pair. (21st June 2019) - Bao, Weijia; Wang, Changle; Wang, Yiping; Sahoo, Namita; Zhang, Lin
Abstract: We demonstrated a highly efficient 2D bending sensor with great direction recognition based on the integration of a titled fiber Bragg grating (TFBG) and a specially designed orthogonal TFBG pair. The low-order cladding modes of the sensor present significant responses to fiber bending magnitude and direction, which is the key to bending direction recognition. Meanwhile, the stable fundamental core mode can be used to monitor the system power and eliminate the temperature effect.